Protocol for a mixed-method cohort study investigating the prevalence and impact of obsessive–compulsive disorder (OCD) in chronic pain rehabilitation - Jonathan Williman; Caroline Bell; Chad Sloley; Edward A Shipton (BMJ Open)
Introduction While there is considerable and growing research in the individual fields of obsessive–compulsive disorder (OCD) and chronic pain, focused research into their potential association remains limited. By exploring this potential association, better theoretical understanding of and better therapeutic approaches to chronic pain management could be developed. The study’s aim is to explore the prevalence and impact of obsessions–compulsions on the experience and rehabilitation of chronic pain among individuals attending different branches of a New Zealand pain service.Methods and analysis This is a cohort study using well-validated questionnaires and semistructured interviews. Participants will be recruited through community pain services from a private rehabilitation-focused company with branches across New Zealand. Participants will complete an OCD screening measure (Obsessive–Compulsive Inventory-Revised (OCI-R)). These results will be used to compare results from the specialist pain services benchmarking electronic Persistent Pain Outcomes Collaboration measure sets, at both participant intake and completion of each Pain Service Programme. Prevalence rates of OCD caseness from the OCI-R will be estimated with 95% CI. Generalised linear regression models will be used to explore differences in pain baseline and outcome factors between those with high and low obsessive–compulsive symptoms. Semistructured interviews, assessed through interpretative phenomenological analysis (IPA), will be used to provide information on lived experiences of individuals with comorbid chronic pain and OCD. This will be supported through the administration of an Obsessive Beliefs Questionnaire 44.Ethics and dissemination Ethical approval has been obtained from the Health and Disability Ethics Committee (HDEC20/CEN/82). Study results will be disseminated at professional conferences and in peer-reviewed journals. A lay summary of findings will be provided to requesting participants or through attendance at a local hui (gathering).Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12621000758808).